The specialty shop : how to create your own unique and profitable retail business - Finell, Dorothy (AMACOM, 2007)
Nearly 2 million small specialty shops start up yearly in the US alone; more than 1.2 million already exist. More than 585,000 go out of business yearly. 900,000 shops are owned by women. These figures from the US Census Bureau point to the huge number of individuals entering this market and how desperately many of them need help to succeed. They also show that both men and women are a strong audience for the book. This book is presented in a very attractive package, with great photos. It is written in a warm, personal writing style. Interviews with and advice from 37 successful shop owners are unique.